Higher Education in China - Gu, Jianmin (Springer Singapore, 2018)
This book offers international readers a comprehensive introduction to higher education in China, and will help readers around the globe make sense of the huge and complex machinery that makes up the university and college sector in China today. It accompanies readers step by step, allowing them to understand the most important aspects of this sector in China - its history and development, its scope and structure, its operational system and management, and its enrollment and employment processes. It also provides an overview of the various levels of higher education in China, namely: specialized higher education, undergraduate education, postgraduate education, research and faculty. In short, the book will tell you what higher education in China is and how it works. While economic globalization and internationalization of higher education have greatly reduced the differences among educational systems in various countries, it cannot be denied that any given country's higher education system needs to be deeply rooted in its culture and traditions. In this book, we highlight several distinctive characteristics of higher education in China, including: the ancient roots and modern history; massive scale; diversity; and centralized management and pragmatic trends.